Penetrasi bank asing terhadap penyaluran kredit bank di indonesia - Ummu Aulia Ramdhani Natsir (JURNAL MANAJEMEN, 2016)
The objective of this study is to analyse the effect of penetration of foreign banks to the credit fund of  banks in Indonesia periode 2009 - 2013. It is also to determine whether the variable liquidity and Gross Domestic Product (GDP) effect on credit. The research data obtained from financial statements that have been published in Bank Indonesia and Badan Pusat Statistik (BPS). By using 495 data from 99 banks in Indonesia, the results of this study show that the Liquidity and GDP has positive effect on credit. Meanwhile foreign bank penetration are negative significant.Keyword: Foreign Bank Penetration, Credit, Loan Growth, Liquidity, and  GDP.